Student Management Model through Character Building: An Effort to Improve the Quality of Education in Vocational High School - Amilda (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Student management is an important aspect in improving the quality of education. This applies to all types of schools, including vocational high schools. This study aims to reveal the student management model implemented by schools and its contribution to improving the quality of education. The research method used is qualitative. The object of the research was conducted at Palembang 2 State Vocational High School. Informants in this study were vice principals for student affairs, curriculum, quality management, student organization coaches, heads of counseling, teachers, and students. Data collection techniques using observation, documentation and interviews. Data were analyzed by means of data reduction, data presentation and conclusions (data triangulation). The results of the study show that the focus of student management is on student development, from being accepted to graduating. There are three models of student management that are carried out, namely: 1) Student management based on coaching 2); flexible management; and 3) Balanced achievement strategy. The characteristic of student management at this school is that student management does not intend to control student behavior, but is directed at how to increase student awareness to control their behavior by using strategies in student development namely “forced, forced, and accustomed”.